Towards a framework of generating sustainable competitive advantages in the integrated public transport systems -IPTS in Colombia. contribution of dynamic innovation capabilities (2017)
Dynamic capabilities of innovation in an organization are seen as necessary to the exploitation of organizational resources towards obtaining sustainable competitive advantages through innovation processes therein can overtake. This article presents a review of the literature to highlight that the number of studies proposed frameworks or methodologies that enable organizational assessment of this potential, are limited. The purpose of this article is to help in reducing this deficiency by proposing a framework of strategic evaluation based on the dynamic capabilities of innovation applicable to the IPTS of Colombia, and at the same time allows the use of available resources in the organization, details of which are presented in the last paragraph of the paper.